Gynostemma pentaphyllum polysaccharides ameliorate non-alcoholic steatohepatitis in mice associated with gut microbiota and the TLR2/NLRP3 pathway - Yue, Si-Ran; Tan, Yi-Yun; Zhang, Lei; Zhang, Bao-Jun; Jiang, Feng-Yan; Ji, Guang; Liu, Bao-Cheng; Wang, Rui-Rui (Frontiers in Endocrinology, 2022)
Recent studies have revealed the pivotal role of gut microbiota in the progress of liver diseases including non-alcoholic steatohepatitis (NASH). Many natural herbs, such as Gynostemma pentaphyllum (GP), have been extensively applied in the prevention of NASH, while the bioactive components and underlying mechanism remain unclear. The aim of this study was to investigate whether the polysaccharides of GP (GPP) have a protective effect on NASH and to explore the potential mechanism underlying these effects. C57BL/6 male mice were fed with a methionine-choline-deficient (MCD) diet for 4 weeks to induce NASH and administered daily oral gavage of sodium carboxymethylcellulose (CMC-Na), low dose of GPP (LGPP), high dose of GPP (HGPP), and polyene phosphatidylcholine capsules (PPC), compared with the methionine-choline-sufficient (MCS) group. Our results showed that the symptoms of hepatic steatosis, hepatocyte ballooning, liver fibrosis, and oxidative stress could be partially recovered through the intervention of GPP with a dose-dependent effect. Furthermore, gut microbiome sequencing revealed that HGPP altered the composition of gut microbiota, mainly characterized by the enrichment of genera including Akkermansia, Lactobacillus, and A2. Moreover, hepatic transcriptome analysis indicated that the anti-inflammatory effect of HGPP might be associated with toll-like receptor (TLR) and nod-like receptor (NLR) signaling pathways. HGPP could inhibit the expression of TLR2 and downregulate the expression of the NLRP3 inflammasome, as well as the pro-inflammatory cytokine tumor necrosis factor (TNF)-α and interleukin (IL)-1β. In summary, GPP could ameliorate NASH possibly mediated via the modulation of gut microbiota and the TLR2/NLRP3 signaling pathway, indicating that GPP could be tested as a prebiotic agent in the prevention of NASH.